Machine Learning Algorithms for Objective Remission and Clinical Outcomes with Thiopurines. (14th March 2017) - Waljee, Akbar K.; Sauder, Kay; Patel, Anand; Segar, Sandeep; Liu, Boang; Zhang, Yiwei; Zhu, Ji; Stidham, Ryan W.; Balis, Ulysses; Higgins, Peter D. R.
Abstract: Background and Aims: Big data analytics leverage patterns in data to harvest valuable information, but are rarely implemented in clinical care. Optimising thiopurine therapy for inflammatory bowel disease [IBD] has proved difficult. Current methods using 6-thioguanine nucleotide [6-TGN] metabolites have failed in randomized controlled trials [RCTs], and have not been used to predict objective remission [OR]. Our aims were to: 1) develop machine learning algorithms [MLA] using laboratory values and age to identify patients in objective remission on thiopurines; and 2) determine whether achieving algorithm-predicted objective remission resulted in fewer clinical events per year. Methods: Objective remission was defined as the absence of objective evidence of intestinal inflammation. MLAs were developed to predict three outcomes: objective remission, non-adherence, and preferential shunting to 6-methylmercaptopurine [6-MMP]. The performance of the algorithms was evaluated using the area under the receiver operating characteristic curve [AuROC]. Clinical event rates of new steroid prescriptions, hospitalisations, and abdominal surgeries were measured. Results: Retrospective review was performed on medical records of 1080 IBD patients on thiopurines. The AuROC for algorithm-predicted remission in the validation set was 0.79 vs 0.49 for 6-TGN. The mean number of clinical events per year in patients with sustained algorithm-predicted remission [APR] was 1.08 vs 3.95 in those that did not have sustained APR [ p < 1 x 10 -5 ]. Reductions in the individual endpoints of steroid prescriptions/year [-1.63, p < 1 x 10 -5 ], hospitalisations/year [-1.05, p < 1 x 10 -5 ], and surgeries/year [-0.19, p = 0.065] were seen with algorithm-predicted remission. Conclusions: A machine learning algorithm was able to identify IBD patients on thiopurines with algorithm-predicted objective remission, a state associated with significant clinical benefits, including decreased steroid prescriptions, hospitalisations, and surgeries.